Branding countries through multicultural events: a quantitative analysis of the impact of the FIFA World Cup 2022 on Qatar’s brand - Kerry, Lucyann; Aguerrebere, Pablo Medina; Burgess, Scott; Chadli, Lakhdar (Frontiers in Communication, 2024)
Private and public companies, as well as public authorities and governments, resort to corporate communication to build trust relationships with their stakeholders and, in this way, reinforce their corporate brands. However, they face different challenges including social transformations and cultural changes. This paper evaluates how the FIFA World Cup 2022 impacted Qatar's brand. To do that, we conducted a review of the literature about corporate communication and nation branding, and then we carried out a quantitative content analysis of how the leading newspapers in the world's most influential countries (United States, China, United Kingdom, France, and Germany) covered this event from a corporate communication perspective. These newspapers were selected based on highest circulation. The results from the analysis showed that media companies from France were the ones making more references to Qatar's History (59); journalists from the United States were the most interested in the Qatar Brand (14); and British newspapers were the ones who published more content about the FIFA World Cup 2022 brand (53).